Analisis Faktor-Faktor yang Mempengaruhi Minat Berwirausaha Siswa SMK Negeri 1 Singaraja Melalui Ekstrakurikuler Kewirausahaan - Luh Juliantari Dewi; I Wayan Suwendra (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2026)
This study aims to determine (1) the factors that influence the entrepreneurial interest of students at SMK Negeri 1 Singaraja through entrepreneurship extracurricular activities, and (2) the most dominant factor influencing the entrepreneurial interest of students at SMK Negeri 1 Singaraja through entrepreneurship extracurricular activities. This research uses a quantitative approach with factor analysis. The population of this study consisted of all Grade X and Grade XI students at SMK Negeri 1 Singaraja, totaling 1,092 students in the 2025–2026 academic year, with a sample of 293 students obtained using the Slovin formula. Data were collected using a questionnaire. The data analysis technique employed was factor analysis with the assistance of SPSS version 16.0 for Windows.Based on the factor analysis, (1) the factors influencing students’ entrepreneurial interest at SMK Negeri 1 Singaraja through entrepreneurship extracurricular activities include motivation, with a variance explained of 73.862%, environmental factors with 14.337%, and entrepreneurial knowledge with 11.801%. (2) The most dominant factor influencing students’ entrepreneurial interest is motivation, with a varimax rotation value of 73.862%.